The Contribution of Pesantren to Sustainable and Social Education: A Narrative Review - Abdulhaviz Hile; Muhammad Arfan Mu’ammar (The Indonesian Institute of Science and Technology Research, 2026)
Pesantren, as Islamic educational institutions, play a crucial role in shaping the character of students (santri) and contributing to community development. This study conducts a narrative review to examine the role of pesantren in sustainable and social education by reviewing literature published between 2015 and 2025. The search strategy included national and international journal databases using keywords such as “pesantren AND sustainable education,” “eco‑pesantren,” and “community empowerment.” Out of 120 identified articles, 52 met the inclusion criteria. Thematic analysis revealed four primary roles of pesantren: (1) integration of sustainable education principles (edu-ecoliteracy), (2) development of eco-pesantren and environmental awareness, (3) social and economic community empowerment, and (4) strengthening of social character and leadership among students. The findings also highlight significant challenges, including limited resources, inadequate policy support, and low digital literacy. This study confirms that pesantren are strategic actors in sustainable and social education, providing recommendations for future research on evaluating eco-pesantren programs, developing sustainable curricula, and integrating educational technology.